Willing But Not Quite Ready: Nurses' Knowledge, Attitudes, and Practices of Research in an Academic Healthcare System. (October 2021) - Nowlin, Sarah; Rampertaap, Kavita; Lulgjuraj, Diana; Goldwire, Tiffany; Cohen, Bevin; Souffront, Kimberly
Abstract : OBJECTIVE: To describe nurses' research knowledge, attitudes, and practices within an academic hospital system. BACKGROUND: Hospitals are investing in research resources to meet Magnet ® goals and advance the science of nursing, but nurses' specific needs for support are not well characterized and may vary by setting. METHODS: We conducted an anonymous online survey of RNs at an academic hospital system in 2019-2020 using the validated Nurses' Knowledge, Attitudes, and Practices of Research Survey. RESULTS: Respondents (N = 99) indicated high willingness to engage in research-related tasks but low or moderate knowledge of and ability to perform them. Knowledge, attitudes, and practices of research increased with level of education, although gaps between willingness to engage versus knowledge and ability persisted even among doctorally prepared nurses. CONCLUSIONS: Research support for clinical nurses should leverage enthusiasm for research and focus on developing and applying specific practical skills, even among nurses with advanced degrees.